Penyelesaian Sengketa Akibat Skimming pada Sektor Perbankan - Titie Syahnaz Natalia (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
This research has purposed to discover the legal protection for a customers which is using ATM card in Indonesia banking systems and to discover the dispute resolution against skimming system in banking sector. This research used normative research method. The conclusion from this study that is the legal protection for customers who is using ATM cards is based Act Number 8 of 1999 concerning Customer Protections and Act Number 21 of 1999 concerning Financial Services Authority especially on The regulation of Financial Services Authority Number 1/POJK.07/2013 concerning Customers Legal Protection on Financial Services. The dispute resolutions for skimming system problems can be resolved by litigation and non litigation.